KOMUNIKASI MOSABOA LAKIOLA DALAM PENYELESAIAN KONFLIK DAN PEMBERDAYAAN MASYARAKAT DI DESA DENTANA, KECAMATAN RIUNG KABUPATEN NGADA, FLORES - Yosef Dema (Jurnal Komunikasi dan Bisnis, 2018)
The vertical conflict experienced by the people of Denatana Village has caused the community to be insecure and the government has difficulty in performing the functions of public service, empowerment and development. The role of Mosaboa Lakiola as local community leaders are needed to resolve vertical conflicts and empower communities. This research is intended to examine the communication of Mosaboa Lakiola to resolve vertical conflicts and empower the community. By using a qualitative approach through interviews with five informants, the results obtained show that the effectiveness of the communication actions of Mosaboa Lakiola in resolving vertical conflicts is determined by the principle-centered approach. Meanwhile, the success of Mosaboa Lakiola's communication actions to empower the community is more determined by real action communication than verbal communication.Keyword: Conflict, Communication, Masaboa Lakiola